Perspektif Remaja terhadap Cyberbullying dalam Pendekatan Schemata Theory - Febriany, Febriany; Handayani, Norlia (IAINU Kebumen, 2023)
Cyberbullying is a serious problem affecting adolescents in the digital environment. Adolescents' understanding, experiences, and attitudes towards cyberbullying have a significant impact on their well-being. This study aims to uncover the process of knowledge, experience, and attitude formation of adolescents related to cyberbullying by using Schemata Theory. The framework in this theory is person schemata, self schemata, role schemata, and event schemata. The method used is descriptive qualitative. Data was obtained through Focus Group Discussion with 6 teenagers. The results show that adolescents have low knowledge about cyberbullying. In addition, there is also a change in the knowledge of adolescents, who previously did not have much knowledge about cyberbullying then changed their knowledge when they held discussions and reflections among their friends. This demonstrated that by exchanging experiences, adolescents are able to conclude and understand a problem that occurs around them. From knowledge and experience, adolescents' attitudes are formed to disagree with cyberbullying behavior. Based on these findings, there is a need for education and awareness about cyberbullying among adolescents, through educational programs that focus on developing empathy and ethical use in the digital environment.